2014
DOI: 10.1111/apa.12704
|View full text |Cite
|
Sign up to set email alerts
|

Infants under 6 months with bronchiolitis are most likely to need major medical interventions in the 5 days after onset

Abstract: Infants under 6 months of age with bronchiolitis were most likely to need MMIs in the first 5 days after disease onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
21
2
Order By: Relevance
“…Shefali-Patel et al [16] observed that healthcare utilization was significantly greater in the RSV compared to the non-respiratory group for respiratory outpatient visits (6.1 vs. 3.8), hospital admissions (2.3 vs. 0.3; P  < 0.001), respiratory-related hospital admission (1.3 vs. 0; P  < 0.001), duration of hospital admission (9.6 vs. 0.4 days; P  < 0.001), pediatric ICU (PICU) admission (1.6 vs. 0 days; P  < 0.001), respiratory primary care visits (12.4 vs. 9.4; P  = 0.07), emergency department visits (3.0 vs. 0.7; P  < 0.001), and respiratory emergency department visits (1.6 vs. 0.1; P  < 0.001). Data from a Finnish study also showed that infants aged <6 months with bronchiolitis were most likely to need major medical interventions (supplementary oxygen, intravenous fluids, intravenous antibiotics or admission to the ICU) in the first 5 days after disease onset [76]. …”
Section: Resultsmentioning
confidence: 99%
“…Shefali-Patel et al [16] observed that healthcare utilization was significantly greater in the RSV compared to the non-respiratory group for respiratory outpatient visits (6.1 vs. 3.8), hospital admissions (2.3 vs. 0.3; P  < 0.001), respiratory-related hospital admission (1.3 vs. 0; P  < 0.001), duration of hospital admission (9.6 vs. 0.4 days; P  < 0.001), pediatric ICU (PICU) admission (1.6 vs. 0 days; P  < 0.001), respiratory primary care visits (12.4 vs. 9.4; P  = 0.07), emergency department visits (3.0 vs. 0.7; P  < 0.001), and respiratory emergency department visits (1.6 vs. 0.1; P  < 0.001). Data from a Finnish study also showed that infants aged <6 months with bronchiolitis were most likely to need major medical interventions (supplementary oxygen, intravenous fluids, intravenous antibiotics or admission to the ICU) in the first 5 days after disease onset [76]. …”
Section: Resultsmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is the most common causative agent in infant bronchiolitis and about 1–3% of each age cohort are treated in hospital for RSV or other viral respiratory infections . The need for intensive care has been reported to vary from 6% to 17% of infants hospitalized for bronchiolitis …”
Section: Introductionmentioning
confidence: 99%
“…In two Finnish studies, the PICU treatment rate was 6% among infants hospitalised for bronchiolitis at ages less than 12 months or less than 6 months . Low birthweight, low gestational age and congenital heart disease are well‐known risk factors for intensive care and respiratory support in infants with bronchiolitis .…”
Section: Discussionmentioning
confidence: 99%
“…Bronchiolitis is the main infectious reason for hospitalisation of less than 12‐month‐old infants when they do not have any notable underlying disease. On average, 1–3% of infants need to be treated in hospital and Finnish studies have reported that 6% of hospitalised infants were treated in a paediatric intensive care unit (PICU) . Bronchiolitis is diagnosed on a clinical basis, and existing guidelines recommend that the cornerstones of bronchiolitis treatment are careful monitoring of oxygenation and fluid intake and supplementing these and providing ventilator support as necessary .…”
Section: Introductionmentioning
confidence: 99%